Catching Up With BIM: A Curriculum Re-Design Strategy - ECE KUMKALE ACIKGOZ (Alanya Hamdullah Emin Paşa Üniversitesi, 2018)
BIM has been discussed widely for enabling collaboration in AEC professions. Its widespread benefits from efficiency to sustainability in design and construction converted it into a primary tool in most AEC education institutions in the last decade. However, Turkey, like a part of central Europe, remains hesitant in this concern. The majority of schools of architecture have conventional curricula based on fragmented areas of expertise studied separately with disconnected contents, teaching methods, and requirements. This separation not only prevents the students from building links between different contents of sustainable design but also increases their workload while decreasing their creative potential. Regarding the necessity for collaboration in the growing complexity of built environments, underdeveloped skills in building links between fragmented databases is eventually becoming a serious problem. This study is expected to demonstrate how provoking the skill to employ BIM can be to integrate creative educational experience in architecture, at the centre of which remains the design studio. The discussion concludes by suggesting pathways to catch up with the growing gap between the global evolutions of interdisciplinary and integral design thinking through the use of BIM in AEC education.